2017
DOI: 10.5194/nhess-2017-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On a reported effect in ionospheric TEC around the time of the 6 April 2009 L'Aquila earthquake

Abstract: Abstract. In a report published in Advances in Space Research, Nenovski et al. (2015) analyse ionospheric TEC data from GPS measurements around the time of 6 April 2009 Mw6.1 L'Aquila (Italy) earthquake. According to the authors, TEC difference (DTEC) calculated from two GPS receivers in central Italy shows a hump-like shape (an increase followed by a decrease) during the hours just before and shortly after the main shock. They maintain that the hump-like shape is anomalous and may be explained as related to t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Differently, a direct correlation between the observed TEC changes and an incoming earthquake has still to be validated by the scientific community. Recent studies 10 , 12 , 20 24 have rather shown that many observed pre-earthquake TEC changes were not associated with the incoming earthquake but were actually driven by either changes in solar and geomagnetic activities, or artifacts related to the adopted procedure of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, a direct correlation between the observed TEC changes and an incoming earthquake has still to be validated by the scientific community. Recent studies 10 , 12 , 20 24 have rather shown that many observed pre-earthquake TEC changes were not associated with the incoming earthquake but were actually driven by either changes in solar and geomagnetic activities, or artifacts related to the adopted procedure of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Curzon et al established a tool focused on understanding how the design of interactive medical devices (such as infusion pumps, monitors, and diagnostic devices help save lives) can support safety [12]. Masci presented a hazard analysis that identified a substantial set of root causes of use hazards in software design, which is general in the sense that the problematic functionalities are common in broad classes of infusion pumps [13]. Masci et al established a model-based risk analysis methodology that helps manufacturers identify and mitigate use hazards in their products at early stages of the development life cycle [14].…”
Section: Introductionmentioning
confidence: 99%